Designing local e-government : the pillars of organizational structure - Patiño Galvan, Israel (Emerald points., 2019)
In the age of digitalization, even the way we govern is adapting. Recently, with the successful implementation of e-governments, the way our systems are organized has changed. Here, Israel Patiño Galvan suggests a specialized design structure as an alternative to the new, digital governments that are becoming increasingly more common. Through a thorough exploration of the history of these structures, and through field research in Mexico, serious deficiencies have been identified in the ways in which these e-governments have been implemented. Instead, Galvan offers a tri-phase solution to designing local governments, placing the direction and division of Information Technologies at the core to support the modernization and optimization process. For researchers and practitioners in public administration, information technologies, or information systems, this is a vital text providing a detailed case study as support for a new organizational system.